Banks' performance enhancement: A framework for valid documentation of credits - Abdul Aziz Khan Niazi; Karamat Azim; Khalil Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
Credit is the business and recovery is the core issue of banks. Documentation of transactions is indispensible to effect complete and timely recovery of banks' credits. The valid credit documentation, that ensures recovery, has fostering impact on the performance of banks. This research study is based on critical review of literature and a framework for the valid documentation of credits has been developed to enhance the performance of banks.
Keywords: 330; Credit; Valid Documentation; Framework; Typification; Dyadic Peculiarities